Cluster analysis of indicators of the enterprise sustainable development - Смачило, Ірина Ігорівна (Technology audit and production reserves, 2013)
The theoretical foundations, scientific and methodological principles to improve management of enterprise sustainable development are grounded. It is proven that the analysis of a number of indicators of enterprises’ activity and their certain factors is a complex mathematical and economic task. The high-quality assessment of the food industry sustainability is suggested to carry out on the basis of grouping enterprises with nearly identical patterns, allowing us to develop the practical recommendations for each group of enterprises. The appropriate means of the calculation system Matlab is suggested to use for such division. For a cluster analysis of the economic situation of a group of enterprises, it is suggested to use the indicators of their sustainable development. By the values of sustainable development indicators, the investigated enterprises are offered to be divided into three groups: those with the indicators of the average levels of sustainable development, those with low levels of sustainable development, and those with high levels of sustainable development. The results of the cluster analysis of these indicators are grounded, and the practical recommendations for each group of enterprises are given: the confectionery industry enterprises which have been studied, in most cases, effectively manage their sustainable development; the enterprises of baking and brewing industries maintain their sustainable development, but its dynamics can be improved; the enterprises of dairy industry is recommended to improve substantially their activities related to the development.